The Role Of Polymorbidity During Covid-19 - Ergashev E.E.; Dzhumabaeva S.E; Dzhumabaev E.S. (Genius Journals, 2023)
We analyzed 340 cases of coronovirus infection in patients hospitalized in the COVID center, taking into account polymorbidity and its contribution to the severity and outcome of the infection. Severe polymorbidity according to CIRS was significantly more common in both men and women (P <0.01), which was significantly more often diagnosed in patients with severe and extremely severe COVID-19, which allows us to confidently speak about the contribution of polymorbidity to the severity of the course of coronovirus infection in men and women. >
Keywords: Coronovirus infection; severity of COVID-19 course; polymorbidity